(untitled) (Journal of Nepal Geological Society, 2011)
This paper deals with foundation characteristics of the soils of different parts of Nepal. In this paper, multiple approaches were adopted to explore foundation characteristic s of the soil. In this study 14 sites from different parts of the country were selected; 2 sites from the hilly region, 2 sites from the inner Terai and 10 sites from the Terai. In each site two test sites were selected. In each test site simplified penetration apparatus (SPA) tests were carried out and were accompanied by the auger tests. Soil samples from different depths in each site were collected for the direct shear test, soil classification, LL PL test, density and other tests and these tests were carried out in laboratory. Bearing capacity of the soils thus obtained from the laboratory was compared with the soil types of certain depth and the Nc value at that depth. From the study it was found that the Nc value depends upon the types of the soil and the compactness of the soils. This study showed that Nc value can be converted in to the ultimate bearing capacity by multiplying the obtained Nc value by the factor of 35 within 80% confidence. Resistivity measurements were carried out only to explore the suitability of the sites for the purposed construction of substations in terms of earthing. Resistivity measurement showed that the sites are suitable for the construction of purposed substations.